Food selection and vertical distribution of pelagic whitefish Coregonus lavaretus (L.) in Lake Tyrifjorden, Norway - Jostein Skurdal; Dag O. Hessen; Dag Berge (Fauna Norvegica)
Zooplankton, almost exclusively cladocerans, was the main food of pelagic whitefish Coregonus lavaretus (L.) in Lake Tyrifjorden, southern Norway. Vertical distribution of whitefish and their zooplankton prey coincided during summer, as both were located close to the surface. In the autumn, however, the whitefish gradually became distributed at deeper layers close to the thermocline, in spite of high surface densities of preferred prey like Daphnia. The downwards migration coincided with an increased number of whitefish with empty stomachs. We suggest that the autumnal downwards migration is a pre-spawning behaviour that advances, and synchronizes gonadal development in mature whitefish.